The Effect of Loan To Deposit Ratio, Net Profit Margin, And Return On Equity, On Stock Returns And Exchange Rates As Moderating Variables In The Banking Sub-Sector On The Southeast Asian Stock Exchange - Sunaryo, Deni; Adiyanto, Yoga; Sa’diyah, Halimatu (Universitas Serang Raya, 2022)
This study aims to determine the effect of Loan to Deposit Ratio, Net Profit Margin and Return on Equty on stock returns with Exchange Rate as a moderating variable. This research uses the object of the banking sub-sector companies in Southeast Asia for the period 2012-2019. The data collected is secondary data with the documentation method in the form of the company's annual report. The analytical tool used to test the hypothesis is IBM SPPS V21. The sampling method used in this study used the Purposive Sampling Technique and obtained 10 companies with a sample of 80 sample data. The analytical techniques used are descriptive statistical analysis, classical assumption test, moderated regression analysis (MRA), multiple linear regression, partial test (t test), and simultaneous test (f test). The results of this study partially conclude that Loan To Deposit Ratio (LDR) has no significant effect on Stock Return, Net Profit Margin (NPM) has no significant effect on Stock Return, and Return On Equity (ROE) has no significant effect on Stock Return. The results of the study simultaneously showed that the Fcount value was 2.891 and Ftable 2.85, meaning that Fcount > Ftable or a significance value of 0.048 <0.05. Thus, Loan To Deposit Ratio (LDR), Net Profit Margin (NPM), and Return On Equity (ROE) simultaneously have a significant effect on Stock Return. The results of the Moderated Regression analysis (MRA) research show that the exchange rate does not moderate the Loan To Deposit Ratio (LDR) on stock returns, and the exchange rate does not moderate the net profit margin (NPM) on stock returns, the exchange rate does not moderate the return on equity (ROE). to Stock Return.